Optimizing the Performance of Water Distribution Networks: Sectorization and Pressure Management for Leakage Reduction - Melina Denardi; Jezabel Bianchotti; Gabriel Puccini; Mario Castro-Gama (Engineering Proceedings)
Sectorization and pressure management are techniques that simplify leak detection and its control in water networks. This article proposes a novel three-stage methodology. First, using complex network theory, it identifies conceptual cuts to form communities. Second, it optimizes District Measurement Areas (DMAs) by reconnecting these cuts, balancing resilience loss and open connections. Third, it reduces network pressure during off-peak hours by installing pressure-reducing valves to create Pressure Management Zones (PMZs). Applied to an academic network and a real network, this approach establishes both DMAs and PMZs, enhancing the supply quality and reducing leakages.